KARDIOCHIRURGIA DOROSŁYCHAssessment of the usefulness of TachoComb in coronary artery bypass graft surgery - Krejca, Michał; Białek, Krzysztof; Krzych, Łukasz; Guc, Michał; Szmagała, Przemysław; Guzy, Michał; Shrestha, Rajesh Bahadur; Bolkowski, Maciej; Bochenek, Krystyna; Bochenek, Andrzej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Aim: The study aimed to assess the influence of the fibrinogen/thrombin-coated collagen patch, TachoComb on the quantity of drainage after the surgery, the length of hospital stay and the number of reoperations due to haemorrhage. Material and Methods: The study was conducted in 105 patients undergoing CABG with the use of extracorporeal circulation and IMA harvesting, hospitalized from 2006 to 2007. Traditional methods of haemostasis were applied in 55 patients and TachoComb was additionally used in 50 subjects to prevent haemorrhage after IMA harvesting. Results: The length of hospital stay was shorter and the quantity of drainage after the surgery was lower, at a statistically significant level (p<0.0001), in TachoComb group patients compared to the control group: 8.86±3.05 days vs. 7.13±1.96 days, and 873.4±279.5 ml vs. 1240.2±499.6 ml, respectively. No statistically significant differences were found between groups in relation to the number of transfusions of blood and haemostatic agents required; however, a growing trend in the quantity of transfusions was observed in the control group. There were no reoperations due to haemorrhage in either group. Conclusions: The application of TachoComb significantly lowers the quantity of postoperative drainage and shortens the length of hospital stay.